RANCANGAN SISTEM INFROMASI MULTIMODA BANDARA INTERNASIONAL I GUSTI NGURAH RAI DALAM MENINGKATKAN PARIWISATA PADA WILAYAH BALI - Shabrina Ramadhani; Lusiana Dewi Kusumayati; Moch Rifa'i (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Bali island has a high tourist attraction for local and international tourists. The number of passengers every long holiday has consistently increased by 50 % or more from the data recorded by the airport. Bali's large number of tourists causes traffoc jam due to the lack of public transportation in the Bali region. With this problem, the local government provided a solution by making public buses such as Sarbagita buses, Trans Dewata buses, and Damri buses. However, many tourists didn't know the existence of this transportation. Although this transportation is low-cost, even free, this transportation is rarely carried passengers. Many tourists chose to use expensive illegal transit due to a lack of information. This study aims to provide information on routes and prices for public transportation to and from the airport so that tourists can plan their journey better. With this information system, the researcher hoped that more tourists would come through Ngurah Rai airport because of the ease of transportation. The data used in this information system is route and price data from public transportation modes operating in the Bali region. In The next stage of the design, researchers used a planning tool in a flowchart using a Flowchart and Unified Modeling Language system (UML). The Researcher developed using a Software Content Management System (CMS). The method used in this research is Research and Development (R & D), with Borg & Gall model development procedure. Some tourists have been testing the development of this multimodal information system applications. It can support the operation of the I Gusti Ngurah Rai International Airport terminal in Bali.